ELGG as an assessment tool in teaching and learning Arabic language - Yahaya , Mohd Firdaus; Md Ghalib, Mohd. Feham (2014)
In line with the development of technology today, the assessment of student’s knowledge and performance in higher learning institutions is not only through the summative approach but also the formative approach where evaluations are carried out consistently throughout the semester. To achieve this, several tools to assess students’ knowledge are made available today, including ELGG which is the focus of this study. This is a new medium to evaluate and assess students meaningfully by tracking the students’ intellectual growth and their learning experience. Furthermore, ELGG is a mediator for peer evaluation where the students’ work can be reviewed by peers and the instructor. Taking this into account, this paper discusses some of the related issues on the use of e-portfolio for educational purposes and as an alternative assessment tool in learning Arabic language. Thirty students were selected to investigate the usefulness of ELGG in teaching and learning. Through ELGG, the teaching and learning process move away from the traditional approach, and invites mutual communication between the instructor and the students, and the students with their peers.